2004
DOI: 10.1002/art.20043
|View full text |Cite
|
Sign up to set email alerts
|

Additional genetic susceptibility for rheumatoid arthritis telomeric of the DRB1 locus

Abstract: Objective. Rheumatoid arthritis (RA) has an estimated genetic contribution of 30-50%, approximately one-third of which arises from the major histocompatibility complex on 6p21.3. Many studies have implicated alleles of DRB1 that encode a shared epitope. However, several recent studies have suggested that additional telomeric genetic influences may exist. In this study, we sought to investigate whether a separate non-DRB1 effect could be detected and to determine its likely location.Methods. We typed 13 single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 35 publications
2
33
1
1
Order By: Relevance
“…Apart from the three TNF family members, the functions of the other proteins are poorly defined, although some evidence for an immune-related role exists for AIF1, 16 LST1 17 and NCR3. 18 Two recent Japanese studies have suggested NFKBIL1 as a susceptibility gene for RA; 14,19 however, this has not been replicated in our British family study 12 or in a Spanish case-control study. 20 The identification of these non-HLA-DR-associated MHC susceptibility genes will require more powerful genetic analyses using dense marker sets and large cohorts.…”
Section: Introductioncontrasting
confidence: 55%
See 2 more Smart Citations
“…Apart from the three TNF family members, the functions of the other proteins are poorly defined, although some evidence for an immune-related role exists for AIF1, 16 LST1 17 and NCR3. 18 Two recent Japanese studies have suggested NFKBIL1 as a susceptibility gene for RA; 14,19 however, this has not been replicated in our British family study 12 or in a Spanish case-control study. 20 The identification of these non-HLA-DR-associated MHC susceptibility genes will require more powerful genetic analyses using dense marker sets and large cohorts.…”
Section: Introductioncontrasting
confidence: 55%
“…This haplotype bears the LST1*2 allele shown to be overtransmitted to RA cases in our family study 12 and also carries HLA-DRB1*15, the allele responsible for the serological DR2 specificity. This specificity is associated particularly with susceptibility to lupus nephritis, 30 and there is considerable evidence from human studies 31 and animal models 32 that this may be mediated by low production of TNF in association with DR2-carrying haplotypes.…”
Section: Gene Expression Analysis Of the Telomeric Mhc D Mewar Et Almentioning
confidence: 64%
See 1 more Smart Citation
“…The TNFA gene is located within the class III region of the MHC. The strong linkage disequilibrium among the Ͼ200 genes of the MHC has made it challenging to delineate the specific contribution of individual MHC genes to the pathogenesis of RA (19)(20)(21). Increased production of TNF␣ has been demonstrated in DR3ϩ and DR4ϩ individuals as compared with DR2ϩ individuals, suggesting genetic variation in levels of TNF␣ production (22).…”
mentioning
confidence: 99%
“…[8][9][10][11][12][13] More recently, dense single-nucleotide polymorphism (SNP)-mapping studies have identified several loci conferring RA susceptibility independently of HLA-DRB1 risk alleles using novel statistical approaches to avoid confounding. [14][15][16] Validation in independent data sets is particularly important to confirm new RA loci in the MHC.…”
Section: Introductionmentioning
confidence: 99%